2015
DOI: 10.15761/imm.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cav2.2 inhibitor on spatial and non-spatial short-term memory

Abstract: Neuronal voltage-gated calcium channels (VGCCs), including Cav2.1 and Cav2.2, mediate the presynaptic machinery responsible for vesicular release of neurotransmitters. However, the role of different VGCCs in neural circuits underlying spatial and non-spatial short-term memory remains poorly understood. Previous report has shown that Cav2.1-mediated signaling is required on spatial memory in a hippocampus-related object location test but has little effect on nonspatial memory in a perirhinal cortex-related obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…We have shown that Cav2.1-regulated glutamatergic signaling in the hippocampus [11] and NAc [12] is important in short-term spatial learning. We have also demonstrated the importance of hippocampal Cav2.2-regurated signaling in spatial short-term memory [13]. Previous reports have showed that Cav2.1 and Cav2.2 are present at high concentrations in the hippocampus and NAc [14] involved in spatial short-term memory formation.…”
Section: Introductionsupporting
confidence: 72%
“…We have shown that Cav2.1-regulated glutamatergic signaling in the hippocampus [11] and NAc [12] is important in short-term spatial learning. We have also demonstrated the importance of hippocampal Cav2.2-regurated signaling in spatial short-term memory [13]. Previous reports have showed that Cav2.1 and Cav2.2 are present at high concentrations in the hippocampus and NAc [14] involved in spatial short-term memory formation.…”
Section: Introductionsupporting
confidence: 72%
“…We showed that a subthreshold dose of CPP significantly decreased the spontaneous alteration behaviors when combined with a subthreshold dose of ω-conotoxin GVIA, although administration of CPP or ω-conotoxin GVIA alone was ineffective in the Y maze test [14,15,17]. The precise regulation of Ca 2+ signaling through Cav2.2 plays an important role in neuronal circuits [3].…”
Section: Resultsmentioning
confidence: 92%
“…We used 5mg/kg as a subthreshold dose of CPP in this study. On the other hand, among mice received intra-hippocampal or intraaccumbens injection of 0, 1, 5, or 10pg/side ω-conotoxin GVIA, mice received 5 or 10pg/side ω-conotoxin GVIA in both regions triggered a spatial short-term memory deficit [14,15]. To examine the effect of subthreshold doses of ω-conotoxin GVIA on Y-maze test, we injected 0, 0.1, 1, or 5pg/side ω-conotoxin GVIA into hippocampus or NAc.…”
Section: Animalsmentioning
confidence: 96%
See 2 more Smart Citations